2022
DOI: 10.52312/jdrs.2022.789
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of helical blade versus lag screw in intertrochanteric fractures of the elderly treated with proximal femoral nail: A meta-analysis of randomized-controlled trials

Abstract: Currently, there are two surgical ways to treat intertrochanteric fractures among the elderly, including extramedullary or intramedullary fixation. [1,2] Although extramedullary fixation is the conventional treatment of intertrochanteric fractures, intramedullary fixation has become a more popular method with the development and progress of intramedullary instruments. [3] The optimal choice between the helical blade and lag screw is still controversial. [4][5][6] Some pieces of literature have reported that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 31 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…We found 3 systemic reviews and meta-analysis which compared the results of helical blade versus screw in the treatment of THF. 21,23,28 Kim et al 23 found a higher overall failure of fixation rate in the helical blade group (pooled OR of 1.88, P = 0.02). The authors compared the different failure mechanism either cut through or cut out for the 2 groups and found a higher failure rate in the helical blade group only for the cut through mechanism of failure.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…We found 3 systemic reviews and meta-analysis which compared the results of helical blade versus screw in the treatment of THF. 21,23,28 Kim et al 23 found a higher overall failure of fixation rate in the helical blade group (pooled OR of 1.88, P = 0.02). The authors compared the different failure mechanism either cut through or cut out for the 2 groups and found a higher failure rate in the helical blade group only for the cut through mechanism of failure.…”
Section: Resultsmentioning
confidence: 97%
“…Between January 2000 and March 2023, of 659 articles screened, 22 met the inclusion criteria and formed the basis of this study. 7,16–36…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations